Determining User Satisfaction in Local E-Governmen Systems: A TAM – Based Prediction Model For The Srikandi Platform - Nur Ilman (Global Research and Collaboration, 2026)
Digital governance transitions in regional municipalities often face unique infrastructural and socio-behavioral barriers compared to metropolitan hubs. This study evaluates the localized implementation of the SRIKANDI application—an integrated digital archiving system mandated by Indonesian Presidential Regulation No. 95/2018—at the Regional Revenue Agency of Luwu Raya (Palopo City). Grounded in the Technology Acceptance Model (TAM), this research employs a quantitative explanatory design to analyze how Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) predict User Satisfaction (SAT). Data were collected via digital surveys from a proportional stratified random sample of N = 200 administrative professionals and analyzed using inferential statistics. The reflective outer model demonstrated robust internal consistency (CR= 0.863–0.912 ; AVE > 0.50). Structural model assessment indicates that the framework explains 54.3% of the variance in user satisfactionsatisfaction, with the model explaining 54.3% of the total variance (R² = 0.543 ,SRMR = 0.061, Q² = 0.387). Hypotheses testing via bootstrapping (5.000 subsamples) revealed that PU exerts the strongest direct effect on satisfaction (Beta (β) = 0.528 , t = 7.412, p< 0.001). Meanwhile, PEOU operates primarily as a critical antecedent to PU (Beta (β) = 0.412, t = 5.873, p < 0.001) while maintaining a smaller direct effect on satisfaction ( = 0.214, t = 2.891, p < 0.05). Usage frequency significantly correlates with satisfaction (p = 0.036) due to habituation. However, 45.7% of the unexplained variance highlights persistent regional design-reality gaps, including localized network instability and senior-staff digital literacy deficits. These findings underscore that while user-friendly interfaces are necessary, long-term institutionalization of E-government in subnational agencies depends heavily on tangible functional utility and targeted literacy mitigation.